Maternidade na prisão: uma análise das relações de apego entre filhos e mães encarceradas - Durigan, Célia Regina Zem (2015)
Children tend to establish with their caregiver, usually the mother, attachment relationships that are fundamental to guide their affective, cognitive and social development. The absence or loss in affective bonds, during early childhood, interferes with the healthy development of children, which affects their relationships. Children of incarcerated mothers may present physical and emotional health problems, as well as social relationship issues, all caused by the instability of the affective bond, which makes them vulnerable and expands risk factors in the course of life. The present study aimed at: describing the social demographics of incarcerated mothers and children; analyzing attachment relationships between mothers and their children within the prison system, and identifying attachment patterns that predominate in said relationships. Eight dyads of children and their mothers participated in the survey, the former being born and raised in the prison environment, whose ages ranged from one to four years. The data collection strategy used was: a semi-structured interview with the mothers, lasting for one hour on average, for collecting data on social-demographics, family and children; and observation sessions, with handwritten records, on the interaction of the children-mothers dyads, using recreational material suitable for such purpose, with a duration of thirty minutes. Four descriptive categories (Secure Attachment, Insecure Attachment, Mother Responsiveness, and Mother Negligence) and two Insecure Attachment subcategories (Avoiding/Uninterested Insecure Attachment and Ambivalent/Resistant Insecure Attachment) arose from the observations made. The overall results of interview analyses and observations indicate the existence of Secure Attachment in five out of the eight dyads (62.5%), with a mean of 37.40 and sd=8.41, and Insecure Attachment in three dyads (37.5%), with a mean of 11.66 and sd=10.60. Dyads were identified as having greater predominance of Ambivalent/Resistant Insecure Attachment, with a mean of 5.00 and sd=4.34, and smaller predominance of Avoiding/Uninterested Insecure Attachment, with a mean of 3.38 and sd=1.69. Pearson’s correlations suggested high significant association scores between Secure Attachment and Mother Responsiveness, with p=0.00; between Ambivalent/Resistant Insecure Attachment and Mother Negligence, with p=0.00; and between Avoiding/Uninterested Insecure Attachment and Mother Negligence, with p=0.02. The obtained data shows that, in spite of difficulties which arise from the studied incarceration context concerning mothering practice, mothers and children establish Secure Attachment relationships which will benefit the dyad. For the children, it solidifies the basis for their development and more positive representations for their future relationships; and, for mothers, it represents mental health and stress improvement, as well as lower recurrence in crime. It is up to public politics to take the commitment of investing in programs which enable incarcerated women to fulfill their roles as mothers, and which grant children their legal rights, aiming at their best interest.